HUMAN CAPITAL MANAGEMENT - Anafiyaeva Zhibek; Abdykerova Gizat Zhanarbekovna; Aykupesheva Dina Malikazhdarovna (Academic Journal of Physical and Chemical Sciences, 2020)
The methods of managing human capital in choosing the best employees, improving the efficiency of employees makes them an indispensable resource for the organization. Human capital management creates a free flow of information between superiors and subordinates, provides the importance of interpersonal communication skills and the development of employees’ personalities. In addition to staff motivation in the form of training and retraining for the effective use of their human capital in the context of innovative transformations, other motivational approaches must be applied. First of all, we are talking about pay. A highly qualified specialist should receive the appropriate salary, which reduces the likelihood of the enterprise losing its valuable human capital. A person, being a physical being, is at the same time a social (social) being, therefore, one cannot reduce a person to economic categories. Man is the bearer of certain natural individual abilities and talents with which nature has endowed him and developed society. A person spends certain physical, material and financial resources on the development of qualities and abilities. Natural abilities and acquired social qualities in their economic role are akin to natural resources and physical capital.